ANALISIS KINERJA SIMPANG BERSINYAL BERLENGAN EMPAT - Mohd Isa T. Ibrahim; Meliyana Meliyana; Saifannur Saifannur (Jurnal Teknik Sipil Unaya, 2015)
Simpang Surabaya is one of the intersections that have high traffic volume. Problems that occur in Simpang Surabaya is the density of traffic flow at peak hours. The objective of  this studyis to analyze the performance of four approaches intersection with traffic signals.Video camera was installed in the data collection then  analyze with Indonesian Highway Capacity Manual (MKJI). The result showed that  at peak hour the highest flow  on the North approache, South approache, East approache, and West approaches respectively 1135 smp hour, 2218 smp hour, 863 smp/hour and 1517 smp hour. Capacity of existing condition in North approache, South approache, East approache, and West approache respectively by 1436 smp/hour, 2806 smp/ hour, 1092 smp/ hour  and 1920 smp/hour. The degree of saturation of each approache is 0.79 and the average delay is 44.92 sec / smp. Based on the results obtained, the Simpang Surabaya is at the service level D.